Impact of the COVID-19 Pandemic on the Clinical Management of People Living with HIV: A Retrospective Study of 246 Patients at a Single Center - Ala-Selek, Selva; Benli, Aysun; Başaran, Seniha; Çağatay, Arif Atahan; Özsüt, Halit (Current HIV Research, 2025)
IntroductionThe COVID-19 pandemic caused disruptions in the diagnosis, follow-up and treatment of non-COVID-19 patients due to the burden on the healthcare system. This may lead to missed early diagnosis opportunities in people living with HIV (PLWH). This study aimed to investigate the effects of the COVID-19 pandemic on the demographic characteristics, clinical and laboratory findings, diagnosis, follow-up, and treatment processes of PLWH, and the frequency of opportunistic infections (OIs), AIDS-defining malignancies (ADMs), and late diagnosis (LD).MethodsIn this study, 246 PLWH were identified. During the pandemic period, the mean age of PLWH was lower (p=0.025), the use of 2 nucleoside reverse transcriptase inhibitor (NRTI) + protease inhibitor (PI/r) decreased (p=0.026) and antiretroviral therapy (ART) adher-ence was higher (p=0.015). LD (48.8% vs. 47.5%) was similar for the two periods, OIs rate (22.6% vs. 18.5%) was lower and ADMs rate (4.8% vs. 6.2%) was higher in the pandemic period. Our study was designed as a retrospective cohort study. Individuals over the age of 18 years who were newly diagnosed with HIV infection in our hospital between 2018 and 2023 were included in the study.ResultsDuring the quarantine period, OIs rate (p=0.008) and hospitalization (p=0.002) decreased significantly. Compared to the pre-pandemic period, there was a decrease in primary school graduates (p=0.043) and Centers for Disease Control and Prevention (CDC) category C applicants (p=0.029) and an increase in university graduates (p=0.027) in the quarantine period. After the quarantine period, there was an increase in hospitalization (p=0.002), CDC category C admissions (p=0.021) and ART adherence (p=0.016). Other data were similar for the three periods.ConclusionIn summary, while the COVID-19 pandemic led to notable changes in patients' characteristics and HIV-related clinical characteristics and treatment, the incidence of LD, OIs and ADMs did not increase significantly. Continued monitoring and adaptation of healthcare services are crucial to managing PLWH effectively in the context of global health crises.
Keywords: HIV/AIDS